Influência da fadiga no controle postural durante o chute em atletas de futsal - Valverde, Ayrton Senna Couto (2019)
Objectives of the study: was to investigate the postural control during the post-fatigue protocol. Methods: A total of 46 male futsal athletes, aged 15-23 years, were divided into two groups: 1) recreational / control athlete (n = 22) and 2) professional athlete group (n = 17) were submitted to functional tests and postural oscillation, using a force platform, during finalization (kick), Sprint test, lactate measurement and Borg stress scale before and after fatigue. Results: A statistical difference was observed only in the Illinois agility test. In relation to the kick test on the platform in the professional athletes group, a statistical difference was shown in the variables AP (p = 0.02, r = 0.33), total displacement (p = 0.04, r = 0.41), (P = 0.05, r = 0.45), AP oscillation velocity (p = 0.05, r = 0.45), lactate (p = 0.0006, r = 1.17, borg scale (p = 0.04, r = 1.07), Sprint test (p = 0.01, r = 0.46), Lactate (p = 0.0003, r = 2.47) (p = 0.0003, r = 1.58) and the Borg scale (p = 0.0001, r = 4.33) (P = 0.04, r = 0.61) and the Borg scale CR10 (p = 0.001 er = 1.72), where the recreational athlete group presented higher values of oscillation . Conclusion: Fatigue was able to influence the dynamic stability of athletes during kicking.